1971
DOI: 10.1042/bj1230773
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of vancomycin and iodovancomycin and their complexes with diacetyl-l-lysyl-d-alanyl-d-alanine

Abstract: Electrometric and spectrophotometric titrations showed vancomycin to contain groups having pK values of about 2.9, 7.2, 8.6, 9.6, 10.5 and 11.7. Of these the four last-named were phenolic. Titration above pH11 and below pH1 was irreversible and antibiotic potency was destroyed. Combination with the specific peptide diacetyl-l-lysyl-d-alanyl-d-alanine hindered the titration of the first three phenolic groups. Spectrophotometric titration of iodovancomycin showed that the phenolic group with pK 9.6 was the one i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(94 citation statements)
references
References 11 publications
(5 reference statements)
8
85
0
Order By: Relevance
“…Vancomycin interferes with cell wall synthesis by combining with the D-alanine residues of the peptidoglycan chain and preventing the cross-link required for stable cell wall synthesis, thus being bactericidal against dividing microbes. [30][31][32] Gentamicin, on the other hand, is an aminoglycoside which inhibits protein synthesis by binding to the 30S subunit of the ribosome. 33,34 Therefore, vancomycin has a direct effect on the cell wall, whereas gentamicin is thought to have an indirect effect on the development and integrity of the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Vancomycin interferes with cell wall synthesis by combining with the D-alanine residues of the peptidoglycan chain and preventing the cross-link required for stable cell wall synthesis, thus being bactericidal against dividing microbes. [30][31][32] Gentamicin, on the other hand, is an aminoglycoside which inhibits protein synthesis by binding to the 30S subunit of the ribosome. 33,34 Therefore, vancomycin has a direct effect on the cell wall, whereas gentamicin is thought to have an indirect effect on the development and integrity of the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Somma et al (1984) reported that teicoplanin, like vancomycin (Best & Durham, 1965;Nieto & Perkins, 1971), binds to cell walls and forms a complex with peptides related to bacterial peptidoglycan, such as…”
Section: Inhibition Of' Teicoplanin-induced Lysis By the Peptide Ac-lmentioning
confidence: 99%
“…Their structure elucidation therefore presents an interesting challenge to current methods, especially since some aspects of the molecular basis for their physiological action are known (Refs. 31,32). …”
Section: Structural Studies On Glycopeptide Antibioticsmentioning
confidence: 99%